Persepsi Perilaku Vandalisme Pada Siswa dan Pemecahan Masalahnnya - Fadkhurosi, Adnan; Ajar, Wendra Deskaria (Edu Berkah Khatulistiwa, 2024)
This research aims to find information regarding the level of perception of vandalism among students at SMK Murni 1 Surakarta. In order to obtain valid and reliable data, researchers used a quantitative descriptive survey research methodology. One thing that makes it unique is the sampling technique and normality test. This research uses a stratified random sampling technique so that it is able to obtain sampling according to field conditions without separating levels, because it has been adjusted and not mixed. The sample used was 209 students from 531 students at SMK Murni 1 Surakarta. The normality test uses a q-q plot normality, and the data taken is categorized as normal. The data collection instrument used was a questionnaire, the data obtained was that 67 students (32%) had a high perception of vandalism, then 119 students (57%) had a moderate perception of vandalism, and 23 students (11%) had a low perception of vandalism. Referring to these results, it can be concluded that the majority of students in the medium-high perception category, students view vandalism as normal and dangerous. This is of course the basis for Guidance and Counseling teachers, as well as related parties, to pay more attention to vandalism behavior by students in the school environment.